2014
DOI: 10.3389/fninf.2014.00083
|View full text |Cite
|
Sign up to set email alerts
|

A case study in connectomics: the history, mapping, and connectivity of the claustrum

Abstract: The claustrum seems to have been waiting for the science of connectomics. Due to its tiny size, the structure has remained remarkably difficult to study until modern technological and mathematical advancements like graph theory, connectomics, diffusion tensor imaging, HARDI, and excitotoxic lesioning. That does not mean, however, that early methods allowed researchers to assess micro-connectomics. In fact, the claustrum is such an enigma that the only things known for certain about it are its histology, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 126 publications
3
28
0
Order By: Relevance
“…Nevertheless, it is generally accepted today that the claustrum exhibits widely distributed reciprocal anatomic projections to virtually all regions of the cortex as well as to many subcortical structures, including the hippocampus, amygdala, and caudate nucleus. Substantial evidence now exists that the major target of claustral projections is the cortex, and that the major input to the claustrum comes from the cortex (see reviews by Smythies et al, 2012Smythies et al, , 2014Baizer et al, 2014;Mathur, 2014;Torgerson and Van Horn, 2014).…”
Section: H a Role For The Claustrum?mentioning
confidence: 99%
“…Nevertheless, it is generally accepted today that the claustrum exhibits widely distributed reciprocal anatomic projections to virtually all regions of the cortex as well as to many subcortical structures, including the hippocampus, amygdala, and caudate nucleus. Substantial evidence now exists that the major target of claustral projections is the cortex, and that the major input to the claustrum comes from the cortex (see reviews by Smythies et al, 2012Smythies et al, , 2014Baizer et al, 2014;Mathur, 2014;Torgerson and Van Horn, 2014).…”
Section: H a Role For The Claustrum?mentioning
confidence: 99%
“…Several recent hypotheses for claustrum function revolve around the highly networked connectivity of the claustrum, which has been demonstrated in humans (Torgerson and Van Horn, ) and rodents (Bota et al, ). Given the claustrum connectivity of prefrontal cortex in the cebus monkey, we recently proposed a novel hypothesis suggesting that the claustrum may play a role in switching between synchrony of task‐negative and task‐positive networks, such as the default mode and central executive or dorsal attention networks (Reser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these general ideas are underpinned by the widespread connectivity of the claustrum with the cerebral cortex. Indeed, the claustrum has been identified as one of the most highly connected regions of the human (Torgerson and Van Horn, 2014) and rodent (Bota et al, 2015) brain. Another attentionrelevant hypothesis regarding claustrum function revolves around coordination of sensory and motor areas between the cerebral hemispheres to facilitate exploratory activity (Smith et al, 2012;Smith and Alloway, 2014).…”
mentioning
confidence: 99%
“…Figure 1 shows in an axial view the anatomical location of the human claustrum. Research in humans using diffusion tensor imaging (DTI) have revealed cortical connections with the claustrum, which possesses projections to A) prefrontal cortex, BA 8,9,10,11,12 and 34;B) visual cortex,BA 17,18,19 and 39;C) sensoriomotor cortex, BA 7, 5, 1/2/3, 4, 6 and 8; and D) language areas BA 44, 45 and 31; as well as with orbitofrontal cortex, temporal cortex, basal ganglia and amygdala (Fernández-Miranda et al, 2008;Milardi et al, 2015;Torgerson and Van Horn, 2014). These results are consistent with the input-output of the claustrum to cortical areas previously reported in animal model studies (Goll et al, 2015).…”
Section: Introductionmentioning
confidence: 99%